Sweet syndrome: a painful reality. (23rd December 2016) - Khan, Uqba; Rizvi, Humaira; Ali, Farman; Lebovic, Daniel
Abstract : Sweet syndrome is a rare disorder that is manifested by constellation of clinical features, including fever, neutrophilic leucocytosis, raised painful plaques on skin and dermal infiltration by neutrophils. Numerous aetiological associations have been reported in the literature, including various haematological malignancies and drugs. Our case was peculiar because of association of capecitabine and Sweet syndrome in rectal cancer. We describe a case of a woman aged 57 years, with recently diagnosed stage III rectal cancer, developed painful erythematous rash over her face along with fever and headache. Skin biopsy was performed which revealed typical findings of Sweet syndrome. She was successfully treated with systemic steroids. Our case was an unusual presentation of Sweet syndrome in a patient with rectal adenocarcinoma treated with neoadjuvant capecitabine.